The synergistic effects on enhancing thermal conductivity and mechanical strength of hBN/CF/PE composite. Issue 40 (10th March 2020) - Xu, Zibo; Lin, Guoming; Sui, Guoxin
Abstract: In this work, a simple and novel method was applied to prepare polymer composites by taking the advantage of melt flow shear force driving orientation of the fillers. By using this method, hexagonal boron nitride/polyethylene (hBN/PE) and hexagonal boron nitride/carbon fibers/polyethylene (hBN/CF/PE) composites were fabricated to be possessed of high thermal conductivity and mechanical properties. A high thermal conductivity of 3.11 W/mK was realized in the composite containing 35 wt% hBN and 5 wt% CF, which was over 1, 200% higher than that of unfilled PE matrix. Under this component, the compressive strength and modulus of hBN/CF/PE composite were determined to be 30.1 and 870.9 MPa, respectively, which were far higher than that of unfilled PE accordingly. The bending performance was also somewhat enhanced. Meanwhile, the bulk resistivity of the composite material reached 2.55 × 10 11 Ω·cm, which was basically the same as that of pure PE. The novel composites with high thermal conductivity, excellent mechanical properties, and controllable electrical insulation could be a potential thermal management material for electrical and electronics industries. Abstract :